2011
DOI: 10.1007/s11661-010-0597-4
|View full text |Cite
|
Sign up to set email alerts
|

A Eutectoid Reaction for the Decomposition of Austenite into Pearlitic Lamellae of Ferrite and M23C6 Carbide in a Mn-Al Steel

Abstract: We discovered a eutectoid reaction in an Fe-13.4Mn-3.0Al-0.63C (wt pct) steel after solution heat treatment at 1373 K (1100°C) and holding at temperatures below 923 K (650°C). The steel is single austenite at temperatures from 1373 K to 923 K (1100°C to 650°C). A eutectoid reaction involves the replacement of the metastable austenite by a more stable mixture of ferrite and M 23 C 6 phases at temperatures below 923 K (650°C). The mixture of ferrite and M 23 C 6 is in the form of pearlitic lamellae. The morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Describing the phase diagrams of Fe-Mn-Al-C is not an easy task. Only in the last 8 years, new phases and phase transformations have been identified [41,44,48,50,62,96] in Fe-Mn-Al-C alloys. Thus, a full description of these phases is still challenging and maybe in some degree premature yet.…”
Section: Phase Constitutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Describing the phase diagrams of Fe-Mn-Al-C is not an easy task. Only in the last 8 years, new phases and phase transformations have been identified [41,44,48,50,62,96] in Fe-Mn-Al-C alloys. Thus, a full description of these phases is still challenging and maybe in some degree premature yet.…”
Section: Phase Constitutionmentioning
confidence: 99%
“…Recent discoveries in the Fe-Mn-Al-C equilibrium constituents have been reported. For instance, the eutectoid reactions; 𝛾 → 𝛼 + 𝑀 23 𝐶 6 [96], 𝛾 → 𝛼 + 𝜅𝑎𝑝𝑝𝑎 𝑐𝑎𝑟𝑏𝑖𝑑𝑒 + 𝑀 23 𝐶 6 [46] and 𝛾 → 𝛾 + 𝛼 + 𝜅𝑎𝑝𝑝𝑎 𝑐𝑎𝑟𝑏𝑖𝑑𝑒 + 𝑀 23 𝐶 6 [49] in the Fe-13.4Mn-3.0Al-0.63C, Fe-13.5-Mn-6.3-Al-0.78-C and Fe-17.9-Mn-7.1-Al-0.85-C steels, respectively. The reader is referred to these references to analyses these phase diagrams that have not been included in the present review.…”
Section: Equilibrium Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there are other non‐cementite carbides which constitute lamellar pearlite with ferrite in high carbon high manganese steel, such as M 23 C 6 carbide, kappa‐carbide etc. . However, it is not clear whether these non‐cementite carbides can also form degenerate pearlite, which needs a further study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that pearlite nucleated preferentially at the austenite grain boundary whether in Fe–Mn–C steel, [ 17–21 ] plain carbon steel, [ 22 ] or Mn–Al steel. [ 23–25 ] However, second‐phase particles precipitated at austenite grain boundaries were activated as intragranular nucleation sites of pearlite when some certain alloying element was added, and the intragranular pearlite had a specific OR with the particles, but had no OR with the austenite grain from which it formed. [ 26–28 ] Although pearlite formed on the proeutectoid M 23 C 6 was observed in 100Mn13 high‐carbon, high‐manganese steel, [ 29 ] it could directly nucleate in austenite grain, and the sites provided by the second‐phase particles has not been found in the steel.…”
Section: Introductionmentioning
confidence: 99%